IMPACTS OF PROPRIOCEPTIVE NEUROMUSCULAR FACILITATION ON FLEXIBILITY IN CHINESE BOXING ATHLETES - Ren,Hao (2023)
ABSTRACT Introduction: Flexibility is one of the essential physical qualities of athletes and Chinese boxing. Proprioceptive neuromuscular facilitation stretching is an effective method to improve flexibility. This method is widely used in various sports. Objective: Analyze the practical effects of stretching by proprioceptive neuromuscular facilitation on Chinese boxing athletes. Methods: This work selected 12 male athletes as research subjects. The athletes were randomly divided into two groups. Flexibility in one group of athletes trained with PNF stretching. Another group of athletes underwent regular training. Mathematical statistics were used to process the flexibility data of the two groups. Results: There were significant differences in the maximum linear velocity in the ankle joint and in the maximum linear velocity in the knee joint between the athletes after training with the experimental stretching (P<0.05). Conclusion: This paper concludes that the application of stretching method with proprioceptive neuromuscular facilitation can improve the flexibility of athletes. The research results of this paper provide background for flexibility training in competition and teaching. Level of evidence II; Therapeutic studies - investigation of treatment outcomes.